Cultural and morphological variability in isolates of Colletotrichum falcatum, causal agent of red rot disease of sugarcane - ., Anuradha; Kashyap, Lenika; Kumar, Rajinder; Singh, Paramjit (Indian Journal of Plant Protection, 2020)
Red rot, caused by Colletotrichum falcatum (Went), is an important disease of sugarcane worldwide. The disease is responsible for elimination of many commercial varieties in the earlier decades. Surveys were conducted to collect the red rot infected canes from different varieties/clones from major sugarcane growing areas of Punjab, Haryana and Uttar Pradesh states of India to identify the variation in the cultural and morphological characteristics of isolates. Fifty seven isolates were differentiated into two distinct groups (light and dark types) based on the colony character. Light coloured, highly sporulating type of fungus predominated in the present study. Forty-two isolates characterized with whitish grey and greyish white colonies were considered as light type isolates. Most of the isolates showed fluffy pattern of growth with medium to high sporulation. Fifteen isolates viz, RI-8, RI-12, RI-15, RI-21, RI-27, RI-28, RI-33, RI-38, RI-41, RI-45, RI-47, RI-51, RI-53, RI-55 and RI-56 had grey colonies with medium or low sporulation and were considered as dark isolates. Conidial size varied among the isolates and measured 27.0-43.0 X 6.5-10.0 µm in their dimensions. The results on cultural/morphological studies revealed that isolates are morphologically dissimilar and there exists a wide variation among the isolates which is the basic method for characterization of different isolates. However, no relationship of the cultural/morphological/characters was detected with respect to the different regions from where the isolates were collected. Hence, to confirm morphological diversity, a combination of cultural/ morphological and molecular techniques is required.